Aminoalcohol-based surfactants (N-(hydroxyalkyl)-N, N- dimethyl N-alkylammonium bromide): evaluation of antibacterial activity and molecular docking studies against dehydrosqualene synthase enzyme (CrtM). Issue 4 (1st March 2021) - Hafidi, Zakaria; Yakkou, Lamia; Guouguaou, Fatima-Ezzahra; Amghar, Souad; Achouri, Mohammed El
Abstract: The present work investigates the antibacterial activity of three quaternary ammoniums surfactants (QACs): (Cn EtOH, Cn PrOH, Cn iPrOH, where n = 12 and 14 carbon atoms against three bacterial strains Escherichia coli (E.coli), Staphylococcus aureus (S. aureus) and Pseudomonas aeruginosa (P. aeruginosa). Results obtained show that the three compounds present the best antibacterial effect against Gram-positive S. aureus bacteria with Minimal Inhibitory Concentration (MIC) between 0.016 and 0.13 mmol/L. The evaluation of the zones of inhibition (IZ) and the Minimum Inhibitory Concentration (MIC) shows an increase as a function of the lengthening of the carbon chain from 12 to 14 carbon atoms for all inhibitors against three bacterial strains. The location of the OH group shows its influence on the availability of N + responsible for the electrostatic interactions with bacterial cell walls, which remains a very important step in the QAC mode of action. It has been found interestingly that for the C12 and C14 series, the Cn EtOH compound exhibits excellent inhibitory activity among the three inhibitors studied against the three bacterial strains. In addition, the theoretical binding mode of the target molecules was evaluated by docking studies against the Dehydrosqualene synthase enzyme (CrtM) (PDB = 3ACX). Graphical Abstract: